PENINGKATAN EKONOMI MASYARAKAT MISKIN MELALUI PEMANFAATAN LIMBAH KELAPA - Yudhistira Adwimurti; Sumarhadi Sumarhadi; Nirwan Mulyatno (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
The purpose of this research is to find out and explain the appropriate technique for processing coconut coir waste in order to produce a product of high economic value and environmentally friendly as well as the development of coco fiber products like what can be produced by SMEs in Keboncau through processing SME waste and strategies to meet foreign market demands. country (export) of derivative products from the coco fiber.This study uses an observational approach or observations and surveys and literature studies. The research was conducted in Keboncau District, Pandeglang, Banten. The location selection was done purposively with the consideration that Keboncau District, Pandeglang, Banten is a center for producing coconut coir waste and is included in the Integrated Agroindustrial Business Area (KUAT) program. The data used in this study are primary data and secondary data. Primary data collection techniques are obtained through an observation, accompanied by notes on the state or behavior of the target object. The data analysis method used in this research is quantitative analysis. The time of the research was carried out in June 2020 to July 2020.Seeing the magnitude of this opportunity, the author took the initiative to provide a solution for processing coconut coir waste in the district of Keboncau, Pandeglang into a ready-to-export product through the use of technology for processing coconut coir waste. So that processed coconut fiber waste products such as door-mats and coir-mats can be exported to Korea and Malaysia to meet the demand for coconut-derived products from America, Australia and Qatar.